Korelasi Kelentukan Pergelangan Tangan dengan Ketepatan Shooting Jarak 7,5 Meter Atlet Petanque Aceh - Novi Lidya Isdarianti; Masri Masri; Agus Wiyanto (YLPK Mahardhika, 2022)
Petanque is a game sport. This sport has basic techniques in the form of pointing and shooting to win the game. A good shooting technique is a guide to becoming a champion. Players who have shooting techniques are strongly influenced by the ability of the physical elements in controlling the petanque ball. One of these elements is wrist flexibility. This study aims to determine the relationship between wrist flexibility and the ability to shoot at a distance of 7.5 meters in Aceh petanque athletes in 2022. The population in this study was the Aceh Petanque Athletes in 2022, totaling 30 people, sampling was carried out by Total Sampling or the overall sample. of the population taken because the subject is less than 100 people. The instruments in this study were: (1) goniometer wrist flexibility test, (2) shooting ability at a distance of 7.5 meters, carried out by shooting a distance of 7.5 meters for 5 times. The data were processed using statistical techniques in the form of calculating the average value (mean), Standard Deviation (SD), product moment correlation, termination coefficient (KP), and hypothesis testing. The results obtained are as follows: there is a relationship between wrist flexibility and shooting ability at a distance of 7.5 meters (r = 0.46). Hypothesis testing shows that tcount = 2.7406 ttable = 2.052 Then there is a significant relationship between wrist flexibility and the accuracy of shooting at a distance of 7.5 meters for athletes in Petanque Aceh in 2022. Based on the calculation results of the contribution between wrist flexibility and accuracy results Shooting distance of 7.5 meters for athletes in Petanque Aceh in 2022 is 21.16%, and the remaining 74.84% is influenced by other factors